Design and Experiment of Deep-position Grabbing Device of Tissue Culture Basket in Facility Agriculture - Li Chen; Liu Juan; Liu Hongliang; Ying Fuqiang (Jixie chuandong)
For the problems such as shallow storage depth,low utilization rate and large amount of labor force required for the existing facility agricultural cultivation frame,a kind of facility agriculture deep-position grabbing device is designed. Through the establishment of three-dimensional model,the feasibility of the program is preliminary determined. Based on the contact dynamics model and the nonlinear continuous collision theory,the calculation method of the collision force during the grasping process is proposed. The dynamics modeling of the impact force between the claw and the object is carried out and the parameters of the handling device are optimized by ADAMS simulation. Finally,the experimental platform is established,the experiments show that the grabbing device can carry the tissue culture baskets on the cultivating rack,and get the optimized movement rule.